Coated tool and cutting tool having the coated tool
By designing a multi-layer structure cover layer in the coated tool, controlling the average particle size and distribution of Al2O3 particles, the problem of high erosion rate during the wear process of existing coated tools is solved, and higher wear resistance is achieved and collapse resistance.
Patent Information
- Application Number
- CN201980078774.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2018-11-29
- Filing Date
- 2019-11-27
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2039-11-27
AI Technical Summary
The cover layer of existing coated tools has a high erosion rate during wear, resulting in insufficient wear and tear resistance.
The coating tool with a multi-layer structure is adopted, in which the thickness of the first and second layers is more than 1 μm and a layer away from the base position, respectively. By controlling the average particle size and distribution of Al2O3 particles, the erosion rate of the second layer is ensured to be 0.4. The erosion rate of the first layer is 1.8 μm/g or less.
It significantly improves the wear resistance and collapse resistance of coated tools, extends the service life of the tool, and reduces friction during the cutting process, thereby improving cutting efficiency.
Smart Images

Figure CN113165082B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a coated tool having a coating layer on the surface of a base body and a cutting tool having the coated tool. Background Art
[0002] Coated tools such as cutting tools are known in which a covering layer including a TiCN layer or an Al2O3 layer is formed on the surface of a base material such as cemented carbide, cermet, or ceramic.
[0003] The covering film in the coated tool requires high wear resistance. The Al2O3 layer generally has higher wear resistance than the TiCN layer. Therefore, for example, in patent document 1, in a coated tool having an Al2O3 layer, the wear resistance of the covered cutting tool is improved by controlling the orientation of the Al2O3 crystals contained in the Al2O3 layer.
[0004] Prior Art Literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2016-137564 Summary of the invention
[0007] The coated tool of the present invention comprises a substrate and a covering layer located on the substrate. The covering layer comprises a first layer having a thickness of 1 μm or more and located near the substrate, and a second layer located farther from the substrate than the first layer. The erosion rate A2 of the second layer measured by colliding a liquid A containing 3 mass % of spherical Al2O3 particles with an average particle size of 1.1 to 1.3 μm in pure water with the second layer is 0.4 μm / g or less. The erosion rate A1 of the first layer measured by colliding the liquid A with the first layer is 1.8 μm / g or less. The cutting tool of the present invention comprises: a tool holder extending from a first end to a second end and having a tool groove on the first end side; and the above-mentioned coated tool located in the tool groove. BRIEF DESCRIPTION OF THE DRAWINGS
[0008] Figure 1 This is a schematic perspective view showing an example of a coated tool according to the present invention.
[0009] Figure 2 It is used to illustrate Figure 1 Schematic diagram of the cross-sectional structure of the covering layer in the coated tool.
[0010] Figure 3 This is a plan view showing an example of the cutting tool of the present invention. DETAILED DESCRIPTION
[0011] <Coated tools>
[0012] The coated tool of the present invention is Figure 1 In the example shown, the main surface is a roughly quadrilateral plate. However, it is not limited to this shape. The coated tool 1 has a first surface 2 (hereinafter referred to as the main surface 2) and a second surface 3, and has a cutting edge 4 at least in a portion where the first surface 2 and the second surface 3 intersect. The first surface 2 is a surface called a rake face, and the second surface 3 is a surface called a flank face. Therefore, it can also be said that a cutting edge 4 is present at least in a portion where the rake face 2 and the flank face 3 intersect.
[0013] In addition, as used to illustrate Figure 2 As shown in the schematic diagram of the cross-sectional structure of the coating layer 7 in the coated tool 1 , the coated tool 1 includes a base 5 and a coating layer 7 located on the surface of the base 5 .
[0014] The material of the substrate 5 constituting the coated tool 1 can be enumerated as cemented carbide, ceramic or metal. As cemented carbide, it can be a cemented carbide containing ferrous metals such as tungsten carbide (WC) and cobalt (Co), nickel (Ni). As other cemented carbides, it can be a Ti-based metal ceramic containing ferrous metals such as titanium carbonitride (TiCN) and cobalt (Co), nickel (Ni). Ceramics can be Si3N4, Al2O3, diamond, cubic boron nitride (cBN). As metal, it can be carbon steel, high-speed steel, alloy steel. Among the above materials, when used as a coated tool 1, the substrate 5 is preferably composed of cemented carbide or metal ceramic in terms of fracture resistance and wear resistance.
[0015] like Figure 2 As shown, the cover layer 7 has a first layer 7a having a thickness of 1 μm or more and located near the substrate 5, and a second layer 7b located farther from the substrate than the first layer 7a. It should be noted that being located near the substrate 5 means being located closer to the substrate 5 than the second layer 7b. The first layer 7a may be in contact with the substrate 5.
[0016] In the coated tool 1 of the present invention, the erosion rate A2 of the second layer 7b is 0.4 μm or less, and the erosion rate A1 of the first layer 7a is 1.8 μm or less.
[0017] It should be noted that the erosion rate refers to the depth of the test object removed by causing a liquid A containing 3% by mass of spherical Al2O3 particles with an average particle size of 1.1 to 1.3 μm dispersed in 100% by mass of pure water to collide with the test object. Therefore, if the erosion rate is small, the wear resistance of the test object is high. In other words, the test object with a small erosion rate is not easy to wear. It should be noted that when measuring the erosion rate, the liquid A can be brought into contact with the surface of the object at approximately right angles and the liquid can be collided at a speed of 98 to 102 m / s.
[0018] For the measurement of the erosion rate, an MSE tester MSE-Al2O3 manufactured by Palmeso can be used.
[0019] The first layer 7a may be, for example, a TiN layer containing a plurality of TiN particles, a TiC layer containing a plurality of TiC particles, a TiCN layer containing a plurality of TiCN particles, or a TiCNO layer containing a plurality of TiCNO particles. The second layer 7b may be, for example, an Al2O3 layer containing a plurality of Al2O3 particles, or a ZrO2 layer containing a plurality of ZrO2 particles.
[0020] The above-mentioned TiN layer, TiC layer, TiCN layer, and TiCNO layer refer to layers containing TiN, TiC, TiCN, and TiCNO as main components, respectively. The main component refers to a crystal containing 50% or more of the crystals contained in each layer. The content can be obtained, for example, by Rietveld analysis using X-ray diffraction.
[0021] The erosion rate A1 of the first layer in the coated tool 1 of the present invention may be 1.5 μm / g or less. In addition, the erosion rate A2 of the second layer in the coated tool 1 of the present invention may be 0.35 μm / g or less. The coated tool 1 having such a structure has better wear resistance and fracture resistance.
[0022] In addition, if Figure 2 As shown, the coated tool 1 of the present invention may further include a third layer 7c as the outermost layer at a position farther from the substrate 5 than the second layer 7b. The third layer 7c may have a thickness of 0.1 μm or more. The erosion rate A3 measured by causing the liquid A of the third layer 7c to collide may be 0.0 to 2.0 μm / g. The coated tool 1 having such a structure has better wear resistance and fracture resistance.
[0023] In addition, the third layer 7c may be a TiN layer containing a plurality of TiN particles, a TiC layer containing a plurality of TiC particles, or a TiCN layer containing a plurality of TiCN particles. If such a third layer 7c is provided, the wear resistance and the fracture resistance are excellent, the friction is small, and the cutting piece can be discharged smoothly.
[0024] The substrate 5 may be a so-called cemented carbide having WC as a main component. Alternatively, the substrate 5 may be a substrate having cBN or diamond as a main component.
[0025] In addition, a base layer (not shown) made of TiN may be further provided between the substrate 5 and the first layer 7a. When the substrate 5 contains components such as Co, C (carbon), and W (tungsten), the base layer has the function of inhibiting the diffusion of these components into the layer existing on the base layer. The base layer may be set to a thickness of 0.1 μm to 1.0 μm.
[0026] In addition, a TiCNO layer (not shown) may be further provided as an intermediate layer between the first layer 7a and the second layer 7b. The intermediate layer may also be composed of a plurality of intermediate layers. The thickness of each intermediate layer is less than 1 μm.
[0027] It should be noted that the structure and thickness of each layer and the shape of the crystals constituting each layer can be measured by observing an electron microscope photograph (scanning electron microscope (SEM) photograph or transmission electron microscope (TEM) photograph) in a cross section of the coated tool 1 .
[0028] In addition, the coated tool 1 is a cutting tool formed at the intersection of the rake face and the flank face that is brought into contact with the workpiece for cutting, and the above-mentioned excellent effect can be exerted. In addition, the coated tool 1 of the present invention can be applied to various uses such as sliding parts, wear-resistant parts such as molds, excavating tools, cutting edges, impact-resistant parts, etc. in addition to cutting tools, and in this case, it also has excellent mechanical reliability.
[0029] Next, an example of a method for manufacturing a cutting tool according to the present invention will be described.
[0030] First, metal powder, carbon powder, etc. are appropriately added to inorganic powders such as carbides, nitrides, carbonitrides, oxides, etc. that can be fired to form a cemented carbide as a matrix and mixed to produce a mixed powder. Next, the mixed powder is formed into a predetermined tool shape by a known forming method such as stamping, casting, extrusion, cold isostatic pressing, etc. The above-mentioned matrix is produced by firing the molded body in a vacuum or a non-oxidizing atmosphere. Then, the surface of the matrix is subjected to grinding and honing of the cutting edge as required.
[0031] Next, a capping layer is formed on the surface by chemical vapor deposition (CVD).
[0032] First, the substrate is placed in a chamber, and a TiN layer is formed as a base layer. The film formation is performed in the following manner: the film formation temperature is set to 830°C, the gas pressure is set to 8kPa, and the composition of the reaction gas is such that titanium tetrachloride (TiCl4) gas is 0.1 to 20% by volume, nitrogen (N2) gas is 20% by volume, and the rest is hydrogen (H2) gas.
[0033] Next, the first layer of the TiCN layer is formed. The film is formed as follows: the film forming temperature is set to 830°C, the gas pressure is set to 9kPa, and as the reaction gas composition, in volume %, the titanium tetrachloride (TiCl4) gas is 5.0-20% by volume, the nitrogen (N2) gas is 10-90% by volume, the acetonitrile (CH3CN) gas is 0.01% by volume to 3.0% by volume, and the rest is hydrogen (H2) gas. At this time, by increasing the content ratio of the acetonitrile (CH3CN) gas in the later stage of film formation compared to the initial stage of film formation, a structure can be formed in which the average crystal width of the titanium carbonitride columnar crystals constituting the first TiCN layer is larger on the surface side than on the substrate side. The thickness of the first layer is 1μm or more. The thickness of the first layer can be set to 3-20μm.
[0034] Next, a first intermediate layer as a TiCN layer is prepared. The film is formed as follows: the film forming temperature is set to 950°C, the gas pressure is set to 9kPa, and the composition of the reaction gas is such that titanium tetrachloride (TiCl4) gas is 10-20% by volume, methane (CH4) gas is 0.5-10% by volume, nitrogen (N2) gas is 10-70% by volume, and the rest is hydrogen (H2) gas. The thickness of the first intermediate layer is less than 1μm.
[0035] Next, the second intermediate layer of the TiCNO layer is formed as follows: First, the film forming temperature is set to 950°C, the gas pressure is set to 9kPa, and the reaction gas composition is such that the titanium tetrachloride (TiCl4) gas is 10-20% by volume, the methane (CH4) gas is 0.5-10% by volume, the nitrogen (N2) gas is 10-20% by volume, the carbon monoxide (CO) gas is 0.1-3.0% by volume, and the rest is hydrogen (H2) gas. The thickness of the second intermediate layer is less than 1μm. In addition, the sum of the thickness of the first intermediate layer and the second intermediate layer is less than 1μm.
[0036] The second layer as the Al2O3 layer is formed as follows: the film forming temperature is set to 950°C to 1100°C, the gas pressure is set to 5kPa to 20kPa, and the composition of the reaction gas is such that aluminum chloride (AlCl3) gas is 5 to 20% by volume, hydrogen chloride (HCl) gas is 0.006 to 2% by volume, carbon dioxide (CO2) gas is 0.01 to 5% by volume, hydrogen sulfide (H2S) gas is 0.001 to 0.01% by volume, and the rest is hydrogen (H2) gas. The thickness of the second layer can be set to 1 to 15 μm.
[0037] Then, the outermost layer, i.e., the third layer, is formed into a TiN layer. The film formation is performed in the following manner: the film formation temperature is set to 1010°C, the gas pressure is set to 10 kPa, and the reaction gas composition is such that the titanium tetrachloride (TiCl4) gas is 0.06 to 5% by volume, the nitrogen (N2) gas is 10 to 30% by volume, and the remainder is hydrogen (H2) gas. The thickness of the third layer can be set to 0.1 to 2 μm.
[0038] It should be noted that, in the above example, an example of providing a first intermediate layer, a second intermediate layer, and a third layer is shown, but the first layer as a TiCN layer and the second layer as an Al2O3 layer may be directly stacked on the surface of the substrate.
[0039] As mentioned above, the coated tool 1 of the present invention has been described, but the present invention is not limited to the above-mentioned embodiment, and various improvements and changes can be made without departing from the scope of the present invention.
[0040] <Cutting tools>
[0041] Next, the cutting tool of the present invention will be described using the drawings.
[0042] like Figure 3 As shown, the cutting tool 101 of the present invention is, for example, Figure 3 from the upper end) to the second end ( Figure 3 The rod-shaped body extends from the lower end of the Figure 3 As shown, the cutting tool 101 includes a tool holder 105 having a tool groove 103 at a first end side (front end side) and the coated tool 1 located in the tool groove 103. The cutting tool 101 includes the coated tool 1, so that stable cutting can be performed for a long period of time.
[0043] The knife groove 103 is a portion for the coated tool 1 to be mounted, and has a seating surface parallel to the lower surface of the tool holder 105 and a restraining side surface inclined relative to the seating surface. In addition, the knife groove 103 is open at the first end side of the tool holder 105.
[0044] The coated tool 1 is located in the tool groove 103. At this time, the lower surface of the coated tool 1 may also be in direct contact with the tool groove 103, and a sheet (not shown) may also be sandwiched between the coated tool 1 and the tool groove 103.
[0045] The coated tool 1 is mounted on the tool holder 105 in such a manner that at least a portion of the portion serving as the cutting edge 7 in the ridgeline where the first surface 3 and the second surface 5 intersect protrudes outward from the tool holder 105. In the present embodiment, the coated tool 1 is mounted on the tool holder 105 by means of a fixing screw 107. That is, the coated tool 1 is mounted on the tool holder 105 by inserting the fixing screw 107 into the through hole 17 of the coated tool 1, inserting the front end of the fixing screw 107 into a threaded hole (not shown) formed in the tool groove 103, and screwing the threaded portions together.
[0046] Steel, cast iron, etc. can be used as the material of the tool holder 105. Steel with high toughness can also be used for these members.
[0047] In this embodiment, a cutting tool 101 used in so-called turning processing is illustrated. As turning processing, for example, inner diameter processing, outer diameter processing, and grooving processing can be listed. It should be noted that the cutting tool 101 is not limited to the tool used in turning processing. For example, the cutting tool used for milling processing can also use the coated tool 1 of the above-mentioned embodiment.
[0048] Example
[0049] First, metal cobalt powder with an average particle size of 1.2 μm is 6 mass%, titanium carbide powder with an average particle size of 2.0 μm is 0.5 mass%, niobium carbide powder with an average particle size of 2.0 μm is 5 mass%, and the rest is tungsten carbide powder with an average particle size of 1.5 μm. The powder is added and mixed in a ratio, and then formed into a tool shape (CNMG120408) by stamping. Then, dewaxing treatment is performed, and the base body composed of cemented carbide is prepared by sintering at 1500°C and 0.01 Pa in a vacuum for 1 hour. Then, the prepared base body is brushed, and R honing is performed on the part that becomes the cutting edge.
[0050] Next, for the above-mentioned cemented carbide substrate, the coating tool was produced by forming a coating layer by chemical vapor deposition (CVD) method, combining the individual film forming conditions shown in Table 1 as described in Table 2 and Table 3. However, between the first layer and the second layer, a first intermediate layer as a TiCN layer and a second intermediate layer as a TiCNO layer were sequentially formed. The thickness of the first intermediate layer was 0.5 μm, and the thickness of the second intermediate layer was 0.1 μm.
[0051] In Table 1, T1 to T5 are film forming conditions for the TiCN layer as the first layer, A1 to A5 are film forming conditions for the Al2O3 layer as the second layer, and S1 to S3 are film forming conditions for the TiN layer as the third layer.
[0052] In Table 1, each raw material gas is marked with a chemical symbol, and the proportion of each raw material gas is expressed in volume %. The thickness of the first layer is 5 μm. The thickness of the second layer is 5 μm. The thickness of the third layer is 0.5 μm.
[0053] The first layers shown in Table 2 are all TiCN layers. In addition, the second layers shown in Table 2 are all Al2O3 layers. In addition, the third layers shown in Table 3 are all TiN layers.
[0054] It should be noted that the first intermediate layer not recorded in the table is formed in the following manner: the film forming temperature is set to 950°C, the gas pressure is set to 9 kPa, and the composition of the reaction gas is 15% by volume of titanium tetrachloride (TiCl4) gas, 5% by volume of methane (CH4) gas, 20% by volume of nitrogen (N2) gas, and the rest is hydrogen (H2) gas.
[0055] In addition, the second intermediate layer 9 not recorded in the table is formed in the following manner: first, the film forming temperature is set to 950°C, the gas pressure is set to 9 kPa, and the reaction gas composition is such that the titanium tetrachloride (TiCl4) gas is 15 volume%, the methane (CH4) gas is 5 volume%, the nitrogen (N2) gas is 15 volume%, the carbon monoxide (CO) gas is 1.0 volume%, and the rest is hydrogen (H2) gas.
[0056] The cross section of the sample including the coating layer was observed by SEM, and the thickness of each layer was measured. Then, Liquid A was made to collide with the coating layer at a speed of 100 m / s in a direction perpendicular to the coating layer, and the erosion rate (μm / g) of each layer was measured.
[0057] Next, the obtained coated cutting tool was used to carry out a wear cutting test and an interrupted cutting test under the following conditions to evaluate the wear life. The test results are shown in Tables 2 and 3.
[0058] <Wear cutting conditions>
[0059] Cutting material: Chrome-molybdenum steel round bar material (SCM435)
[0060] Tool shape: CNMG120408
[0061] Cutting speed: 300m / min
[0062] Feed speed: 0.3mm / rev
[0063] Incision: 1.5mm
[0064] Others: Use water-soluble cutting fluid
[0065] Evaluation item: The time it takes for the base material to be exposed on the rake face due to the progress of front wear
[0066] <Interrupted cutting conditions>
[0067] Workpiece: 4-grooved round bar of chrome-molybdenum steel (SCM440)
[0068] Tool shape: CNMG120408
[0069] Cutting speed: 300m / min
[0070] Feed speed: 0.3mm / rev
[0071] Incision: 1.5mm
[0072] Others: Use water-soluble cutting fluid
[0073] Evaluation Item: Number of impacts applied to the blade tip before the blade tip is damaged
[0074] [Table 1]
[0075]
[0076] [Table 2]
[0077]
[0078] [Table 3]
[0079]
[0080] As shown in Table 2, Samples No. 1, 2, 6, and 7 having a first layer with an erosion rate A2 of 0.4 μm / g or less and an erosion rate A1 of 1.8 μm / g or less had excellent wear resistance.
[0081] Furthermore, as shown in Table 3, Samples Nos. 26 and 28, which also had the third layer as the outermost layer with a corrosion rate A3 of 2.0 μm / g or less, had more excellent wear resistance.
[0082] Description of reference numerals:
[0083] 1···Coated tools
[0084] 2···Rake face
[0085] 3···Flanking surface
[0086] 4···Cutting edge
[0087] 5. Matrix
[0088] 7. Covering layer
[0089] 7a···First floor
[0090] 7b···Second floor
[0091] 7c···Third floor
[0092] 101···Cutting tools
[0093] 103···Knife groove
[0094] 105···Knife holder
[0095] 107···Fixing screw.
Claims
1. A coated tool used in a cutting tool, wherein the coated tool comprises a substrate and a covering layer located on the substrate, wherein: The cover layer includes a first layer having a thickness of 1 μm or more and located near the substrate, a second layer located farther from the substrate than the first layer, and a third layer as an outermost layer. The first layer is any one of a TiN layer containing 50 mass % or more of TiN, a TiC layer containing 50 mass % or more of TiC, and a TiCN layer containing 50 mass % or more of TiCN, The erosion rate A2 of the second layer measured by causing a liquid A containing 3 mass % of spherical Al2O3 particles having an average particle size of 1.1 to 1.3 μm dispersed in pure water to collide with the second layer at a speed of 98 to 102 m / s is 0.35 μm / g or less. The erosion rate A1 of the first layer measured by causing the liquid A to collide with the first layer at the speed is 1.5 μm / g or less, The erosion rate A3 of the third layer measured by causing the liquid A to collide with the third layer at the speed is 0.0 to 2.0 μm / g, The third layer is any one of a TiN layer, a TiC layer and a TiCN layer.
2. The coated tool according to claim 1, wherein: The second layer is any one of an Al2O3 layer and a ZrO2 layer.
3. The coated tool according to claim 1, wherein: The matrix is WC-based cemented carbide.
Citation Information
Patent Citations
CVD coated cutting tool
JP2016137564A
Surface coated cutting tool with excellent chip resistance
CN102596456A
Surface-coated cutting tool
KR1020070041791A
Doctor blade
US20110219971A1
Hard coating, hard coating-covered member, and method for producing hard coating
WO2017163972A1